A personalized approach in the pregnancy management and the method of delivery in patients with impaired carbohydrate metabolism - E. V. Shaposhnikova; D. A. Maiseenko; Yu. E. Semenova; K. I. Mentsik (Лечащий Врач)
Background. Patients with impaired carbohydrate metabolism are at risk of developing diabetic fetopathy, premature birth and surgical delivery. Strict follow-up to the relevant clinical guidelines for the diagnosis of carbohydrate metabolism disorders, pregnancy management, the choice of the planned date and method of delivery are aimed at reducing the risk of obstetric and perinatal complications.Objective. To analyse perinatal outcomes, duration and method of delivery in patients with impaired carbohydrate metabolism over the past 5 years (2018, 2022).Materials and methods. The birth charts of 885 patients with carbohydrate metabolism disorders who were hospitalised prenatally and delivered in the maternity hospital were analysed.Results. The number of patients with carbohydrate metabolism disorders increased 2.3 times over the past 5 years, from 13,6% (315/2320) in 2018 to 30,9% (570/1840) in 2022 (RR = 0,58; 95% CI 0,53-0,64; p < 0,001), due to patients with GDM, the number of births increased by 2,5 times in relation to the total number of deliveries, from 11,7% (271/2320) in 2018 to 29,3% (540/1840) in 2022 (RR = 0,55; 95% CI 0,49-0,60; p < 0.001). Structure analysis of gestational complications showed that the incidence of diabetic fetopathy is 2,4 times less often: 7,9% (45/570) in 2022 vs 19,4% in 2018 (61/315) (RR = 1,77; 95% CI 1,46-2,14; р < 0,001), a decrease in moderate preeclampsia by 2,3 times is determined. Reduction in the frequency of perinatal complications allows you to prolong pregnancy to full term. The number of preterm births decreased by 5%, from 6,4% (20/315) in 2018 to 1,4% (8/570) in 2020 (RR = 2.07; 95% CI 1,61-2,67; р < 0,05). The number of planned births increased by 18,6%, from 25,1% (79/315) in 2018 to 43,7% (249/570) in 2022 (RR = 0.57; 95% CI 0,46-0,70; р < 0,001). It reduced the percentage of caesarean sections by a factor of 3,2, from 46,9% (148/315) in 2018 to 14,7% (84/570) in 2022 (RR = 2,49; 95% CI 2,12-2,94; р < 0,001).Conclusion. Timely diagnosis of carbohydrate metabolism disorders and correctly chosen management tactics are foundation for likelihood vaginal delivery at full term.